Conversion of Barren Saline Soil to Cultivation Changes Soil Enzymes Activities: Effects of Irrigation Water Quality - Arvind Kumar Rai (Journal of the Indian Society of Soil Science, 2023)
Soil biological properties are early indicators of management-induced changes in soil processes. The field experiment investigates the effect of different irrigation water qualities [SW- saline water (8.0 dS m-1); GW- good quality water (0.8 dS m-1); CW- conjunctive use of saline water (8.0 dS m-1)] on soil enzymes activities and their resistance to seasonal variation in a barren saline agroecosystem converted to sorghum– wheat cropping system. A higher salinity build-up was recorded in SW irrigated plots followed by CW and GW (p< 0.05). The leaching of the salts increased soil pH. Dehydrogenase activity (DHA) was higher in plots irrigated with GW, while, alkaline phosphatase activity (ALP) was higher in SW (p< 0.05). Enzymes DHA and α-glucosidase (AG) were more sensitive to conversion from fallow to cultivation, whereas, urease and AG were more sensitive to seasonal change under cultivated soils. The DHA, ALP, and β- glucosidase (BG) showed high resistance to seasonal changes under different irrigations. The multivariate analysis recommended that the land-use conversion, irrigation water quality, and seasonal changes had an impact on soil enzyme activities. Therefore, it needs to be considered in attribute selection for developing soil health index of production system under transient state.